Freezing time prediction for film packaged food - Chin, S. W.; Spotar , Sergey Y. (Federation of Engineering Institutions of Islamic Countries, 2006)
A freezing process of the film packaged slab-shaped food was studied by modeling and experimentally. Food samples temperature histories were determined by carrying out a freezing operation in an air-blast freezer. A freezing model was developed for an asymptotic case when film and food perform independently; thus, assuming the void between the food and the film are caused by appreciable food density change. Advanced model gives freezing time prediction that agrees reasonably well with the observed data.